1996
DOI: 10.1074/jbc.271.36.21732
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Putative Effector for Cdc42Hs with High Sequence Similarity to the RasGAP-related Protein IQGAP1 and a Cdc42Hs Binding Partner with Similarity to IQGAP2

Abstract: Glutathione-dependent detoxification reactions are catalyzed by the enzyme glutathione S-transferase and are important in drug resistance in organisms ranging from bacteria to humans. The yeast Issatchenkia orientalis expresses a glutathione S-transferase (GST) protein that is induced when the GST substrate o-dinitrobenzene (o-DNB) is added to the culture. In this study, we show that overproduction of the I. orientalis GST in Saccharomyces cerevisiae leads to an increase in o-dinitrobenzene resistance in S. ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
183
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(193 citation statements)
references
References 38 publications
9
183
1
Order By: Relevance
“…Mammalian IQGAP1 was also identified as a CDC42 target, acting through its C-terminal domain (Brill et al, 1996;Kinoshita et al, 1997;McCallum et al, 1996;Kuroda et al, 1996), and the domain structure of yeast and mammalian IQGAPs is conserved (Epp and Chant, 1997;Lippincott and Li, 1998;Osman and Cerione, 1998), implying a conserved function. IQGAP1 is a member of a three-isoform family of proteins that also includes IQGAP2 (Yamashiro et al, 2003) and IQGAP3 .…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian IQGAP1 was also identified as a CDC42 target, acting through its C-terminal domain (Brill et al, 1996;Kinoshita et al, 1997;McCallum et al, 1996;Kuroda et al, 1996), and the domain structure of yeast and mammalian IQGAPs is conserved (Epp and Chant, 1997;Lippincott and Li, 1998;Osman and Cerione, 1998), implying a conserved function. IQGAP1 is a member of a three-isoform family of proteins that also includes IQGAP2 (Yamashiro et al, 2003) and IQGAP3 .…”
Section: Introductionmentioning
confidence: 99%
“…Several proteins that are structurally related to IQGAP1 have been described. The most similar proteins in terms of primary sequence and domain organization are IQGAP2, a liver-enriched protein in mammals (3,10), and a Hydra protein that has been implicated in tentacle formation (11). Additional IQGAP1-related proteins have been found in Dictyostelium (12)(13)(14), and Saccharomyces cerevisiae (15)(16)(17).…”
mentioning
confidence: 99%
“…Analysis of its predicted amino acid sequence revealed that the IQGAP1 polypeptide does contain a GAP-related domain, as well as four putative calmodulin-binding IQ motifs (1). Although the GAP-related domain of IQGAP1 does not seem to have GAP catalytic activity (1,2), it does form part of a region that preferentially binds to activated forms of the small G proteins, Cdc42 and Rac1 (2)(3)(4). IQGAP1 consists of two identical 190-kDa subunits that associate with cortical actin filaments in cultured mammalian cells and cross-links actin filaments into bundles and gels in vitro (2,(5)(6)(7).…”
mentioning
confidence: 99%
“…Like IQGAP1, IQGAP2 binds to Cdc42 in its GTP-bound state and inhibits intrinsic and RhoGAP-stimulated GTP hydrolysis [although the nucleotide dependence of the interaction between IQGAP2 and Cdc42 is not as well established as for IQGAP1 (5,25,33,34)]. Recently, IQGAP2 was proposed to be a Cdc42-dependent regulator of parietal cell HCl secretion (46).…”
mentioning
confidence: 99%